Applications of bone regenerative medicine in the foot and ankle: mechanisms, technologies, and therapeutic advances - Yang, Lianbo; Li, Yijie; Wang, Tianqi; Zhao, Zhuo; Li, Wang; Lv, Jinghang; Chen, Haoran; Qi, Zhaodong; Wang, Xinming; Bao, Wenchi; Liang, Haidong (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundFoot and ankle diseases significantly impact quality of life, with regenerative medicine emerging as a promising approach. A comprehensive evaluation of both efficacy and safety is paramount for its clinical translation.MethodsA comprehensive literature search was conducted in PubMed using keywords “regenerative medicine” and “foot and ankle” (as of 31 December 2024). Studies were categorized by technology and disease.ResultsPRP and HA showed short-term efficacy in talar cartilage repair; stem cells enhanced functional recovery in ankle osteoarthritis. 3D printing enabled personalized implants. Exosomes and AI were identified as future directions. However, the reporting of safety data was often sporadic and non-standardized, highlighting the need for more systematic monitoring in future studies.ConclusionRegenerative therapies demonstrate potential but require further validation through robust trials that prioritize standardized safety reporting alongside efficacy outcomes. Gaps in exosome isolation, long-term safety, and clinical translation need addressing.